Biopolymer Nanovehicles for Oral Delivery of Natural Anticancer Agents. (3rd December 2022) - Falsafi, Seid Reza; Wang, Yong; Ashaolu, Tolulope Joshua; Sharma, Minaxi; Rawal, Shruti; Patel, Kaushika; Askari, Gholamreza; Javanmard, Shaghayegh Haghjooy; Rostamabadi, Hadis
Abstract: Cancer is the second leading cause of death throughout the world. Nature‐inspired anticancer agents (NAAs) that are a gift of nature to humanity have been extensively utilized in the alleviation/prevention of the disease due to their numerous pharmacological activities. While the oral route is an ideal and common way of drug administration, the application of NAAs through the oral pathway has been extremely limited owing to their inherent features, e.g., poor solubility, gastrointestinal (GI) instability, and low bioavailability. With the development of nano‐driven encapsulation strategies, polymeric vehicles, especially those with natural origins, have demonstrated a potent platform, which can professionally shield versatile NAAs against GI barricades and safely deliver them to the site of action. In this review, the predicament of orally delivering NAAs and the encapsulation strategy solutions based on biopolymer matrices are summarized. Proof‐of‐concept in vitro/in vivo results are also discussed for oral delivery of these agents by various biopolymer vehicles, which can be found so far from the literature. Last but not the least, the challenges and new opportunities in the field are highlighted. Abstract : Cancer is the second leading cause of death throughout the world. With the development of nano‐driven encapsulation strategies, polymeric vehicles, especially those with natural origins, have demonstrated a potent platform, which can professionally shield versatile nature‐inspired anticancer agents against gastrointestinal barricades and safely deliver them to the site of action.